Gastric Acid Diagnosing Expert System Using Certainty Factor Method - Dimas Prasetyo (Institute of Computer Science (IOCS), 2020)
Ulcer disease or stomach acid is a psychomatic disease (disease of the mind and body) or it could be an infectious disease caused by bacteria that cause infection in the stomach. Acid reflux can also occur due to irregular eating patterns. At least sufferers are aware about maintaining their diet and choosing food to reduce symptoms of stomach acid. In this case the author tries to create an existing system by proposing an expert system system to diagnose gastric acid disease using the certainty factor method. The certainty factor method is a method to prove whether a fact is certain or uncertain. The main goal in designing this system is to determine the symptoms of gastric acid and how to treat it.